PRO DAN KONTRA UNDANGUNDANG ANTI PORNOGRAFI DAN PORNOAKSI - Yulianti, Rahmani Timorita (Islamic University of Indonesia, 2006)
It is actually ironically, in one hand Indonesia society talking about the morality of nation, on the other hand, this nation ignore pornography and pornoaction.Instead, Some people refuse the proposed academic manuscript regarding pornography and pornoaction. Apart from the pros and cons toward the act of pornography and pornoaction, pornography and pornoaction denote ophyum in the living of society. According to the writer of the following article, because of majority of Indonesian population are Moslem, so Indonesian Moslem should participate in the discourse of the act. But, how to search for horizon wisely, either in term of culture or the principles of Islam. Kata kunci: pornogarfi, pornoaksi, Islam, budaya, dan Indonesia.